2022
DOI: 10.4314/jae.v26i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Capability of Extension Agents in Disseminating Climate Change Information in Delta State Nigeria

Abstract: The study assessed the capability of extension agents in disseminating Climate Change (CC) information in Delta State, Nigeria. A multi-stage procedure was used in selecting 60 respondents. Data were collected on respondents’ capacity for outreach to farmers; existence of linkage on CC and sources of information on CC, constraints to building capacities for outreach and strategies to strengthen capacities. Mean, percentage, were used for analysis. Findings showed the existence of training on CC (23.3%) and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…In Table 5, the most accepted strategies identified to strengthen capacities of the extension agents are: appraisal of the agricultural extension policies (3.716), restructuring of extension agents' education and trainings (3.618), adequate resourcing of coordination mechanism and supervision (3.250), appropriate funding of extension activities (3.559), giving incentives to motivate extension workers (3.397), planning of seminars and workshops to enhance the extension agents' proficiency (3.294). This finding corresponds with the report of Ozioko et al (2022) who identified strategies for building capacities as review of agricultural extension policies, reformation of basic education to boost job motivation, and organization of conferences and seminars to increase competence of extension agents.…”
Section: Strategies To Building Capacities Of the Extension Agentssupporting
confidence: 88%
See 1 more Smart Citation
“…In Table 5, the most accepted strategies identified to strengthen capacities of the extension agents are: appraisal of the agricultural extension policies (3.716), restructuring of extension agents' education and trainings (3.618), adequate resourcing of coordination mechanism and supervision (3.250), appropriate funding of extension activities (3.559), giving incentives to motivate extension workers (3.397), planning of seminars and workshops to enhance the extension agents' proficiency (3.294). This finding corresponds with the report of Ozioko et al (2022) who identified strategies for building capacities as review of agricultural extension policies, reformation of basic education to boost job motivation, and organization of conferences and seminars to increase competence of extension agents.…”
Section: Strategies To Building Capacities Of the Extension Agentssupporting
confidence: 88%
“…lack of distinct agricultural policy (3.254), use of obsolete facilities (3.13), weak staff training on climate change (3.059), meagre funding of rural development program (3.07), and lack of equipment to implement skills learnt at training (2.82).This result agrees with Onoh et al (2023) who affirmed that limited access to resources, lack of education and training opportunities are key barriers to building capacity of women in agriculture. This result is also in line with the findings ofOzioko et al (2022) who found that absence of well-defined agricultural policy, poor funding of rural development program, lack of human resources and poor staff training are the major constraints to building capacities for outreach by extension agents.…”
supporting
confidence: 89%
“…lack of distinct agricultural policy (3.254), use of obsolete facilities (3.13), weak staff training on climate change (3.059), meagre funding of rural development program (3.07), and lack of equipment to implement skills learnt at training (2.82).This result agrees with Onoh et al (2023) who affirmed that limited access to resources, lack of education and training opportunities are key barriers to building capacity of women in agriculture. This result is also in line with the findings ofOzioko et al (2022) who found that absence of well-defined…”
supporting
confidence: 93%
“…This study is concerned with community outreach. It typically refers to programs or initiatives where extension agents actively engage with farmers or community to address specific needs or provide support (Ozioko, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the number of the extension staff is in line with the Kristin et al (2019) who stated that it will reduce the extension-farmer ratio and therefore makes it possible for farmers to be easily reached by the extension workers. While provision of incentives to extension staff was in agreement with findings of Ozioko, et al (2022). Such incentives perhaps involve paying of salaries and allowances when due as it is hoped that doing this may go a long way in motivating the extension staff in their jobs and as well making themselves and their technology more available to the farmers.…”
Section: Strategies That Could Improve Extension Service Access To Fa...supporting
confidence: 52%